How to train your dragon book 10 : how to seize a dragon$1 (Bs jewel /s - Cowell, Cressida (New York : Little, Brown and Company, 2013)
When Hiccup Horrendous Haddock III is captured by the Dragon Rebellion, he must outwit traitors, discover a powerful jewel, and face the darkest dangers yet in order to save both dragons and Vikings.
Originally published in the U.K. by Hodder Children$1 (Bs Books, 2012.s
Keywords: Vikings -- Fiction; Dragons -- Fiction; Quests (Expeditions) -- Fiction; Prophecies -- Fiction; Friendship -- Fiction; Fathers and sons -- Fiction; Humorous stories